A constituição dos ethé de Amaro Neto, do Balanço Geral/ES : retórica, humor e encenação - Gazzoli, Janine Aparecida Bessa Banhos (2015)
ocused on building persuasive speeches, the rhetoric resorts the exploration of reason and affectivity as the means to achieve success. In this sense, humor is very relevant in many rhetorical actions. Based on the above, this research investigates how the ethe of Amaro Neto, anchor Balance Geral/ES, are made through rhetorical, humorous and prosodic devices and performers expedients (kinesic and proxemic). Our hypothesis is that humor is the main argumentative strategy used by this speaker in the persuasion process. To this end, we take as the object of analysis six clippings videos broadcast on TV Vitória in the years 2009-2011, of great repercussion on the internet. This study aims not only to identify the techniques deployed by Amaro Neto to generate humorous sense and observe how these resources are able to build certain images of the speaker in question, but also how the humour interacts with other argumentative techniques – case of lexical choices, the arguments and rhetorical figures – to move the attention of the audience. To produce this work, we relied mainly on theoretical assumptions of aristotle's Rhetoric (ARISTOTLE, 1991, 2005, 2007), the New Rhetoric (PERELMAN; OLBRECHTSTYTECA, 2005; MEYER, 2007; REBOUL, 2004; AMOSSY, 2013) and scholars of humour (BERGSON, 2007; FREUD, 1905; RASKIN, 1985; TRAVAGLIA, 1990, 1992; POSSENTI, 1998, 2013; CARMELINO, 2012). The analyzes, which take into account the verbal and non-verbal that make up the clippings, show that Amaro Neto builds the irreverent actor ethos to raise and maintain the attention of your audience.